2017
DOI: 10.4103/2249-4863.219992
|View full text |Cite
|
Sign up to set email alerts
|

Association of social anxiety disorder with depression and quality of life among medical undergraduate students

Abstract: Objective:Social anxiety disorder (SAD), (also known as social phobia), is characterized by intense fear of social interaction and often associated with social avoidance and impairments. There is high risk for depression, substance use disorder, and suicide among them.Subjects and Methods:It is an observational, cross-sectional, single centered, questionnaire-based study assessing the frequency of SAD and depression and their possible association with quality of life among 290 consenting medical undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
1
32
2
2
Order By: Relevance
“…In the present study, there was a significant indirect correlation between overall QOL score and all of its subdomains with depression score. Many studies showed that by reducing depression and increasing mental health, people's QOL increases,[ 31 32 33 34 ] which is consistent with the results of our study. Paro et al .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, there was a significant indirect correlation between overall QOL score and all of its subdomains with depression score. Many studies showed that by reducing depression and increasing mental health, people's QOL increases,[ 31 32 33 34 ] which is consistent with the results of our study. Paro et al .…”
Section: Discussionsupporting
confidence: 92%
“…In a Korean study published in 2007, 9.4% of medical students were found to be currently depressed and only 9.7% of them (0.9% of the entire sample) were correctly treated for depression. According to different severity levels, depression of Indian medical students ranked from 0.7% to more than half (Goel et al, 2016;Kumar et al, 2017;Ratnani et al, 2017). No data on antidepressant consumption of medical students of Asia, Africa or South-America and Latin-America is available to date.…”
Section: Discussionmentioning
confidence: 99%
“…This was later simplified to 26 questions (WHOQOLbref) 46) . Quality of life measured by the WHOQOL-bref showed an association with sleep disturbances 5,29,40) .…”
Section: Introductionmentioning
confidence: 93%